School Choice during a Period of Radical School Reform: Evidence from the Academy Programme - Marco Bertoni; Stephen Gibbons; Olmo Silva (Institute of Labor Economics (IZA), 2017)
Education policy worldwide has sought to incentivize school improvement and facilitate pupil-school matching by introducing reforms that promote autonomy and choice. Understanding the way in which families choose schools during these periods of reform is crucial for evaluating the impact of such policies. We study the effects of a recent shock to the English school system – the academy programme – which gave existing state schools greater autonomy, but provided limited information on possible expected benefits. We use administrative data on school applications for three cohorts of students to estimate whether academy conversion changes schools' popularity. We find that families – particularly non-poor, White British ones – rank converted schools higher on average. We investigate the likely mechanisms that could give rise to our findings. The patterns we document suggest that families combine academy conversion with home-school distance and prior information on quality and popularity as a heuristic to inform school choice.
Keywords: I21; H75; 330; school reform; choice and autonomy; preference formation